Cyclic mechanical stimulation rescues achilles tendon from degeneration in a bioreactor system. Issue 12 (17th July 2015) - Wang, Tao; Lin, Zhen; Ni, Ming; Thien, Christine; Day, Robert E.; Gardiner, Bruce; Rubenson, Jonas; Kirk, Thomas B.; Smith, David W.; Wang, Allan; Lloyd, David G.; Wang, Yan; et al.
ABSTRACT: Physiotherapy is one of the effective treatments for tendinopathy, whereby symptoms are relieved by changing the biomechanical environment of the pathological tendon. However, the underlying mechanism remains unclear. In this study, we first established a model of progressive tendinopathy‐like degeneration in the rabbit Achilles. Following ex vivo loading deprivation culture in a bioreactor system for 6 and 12 days, tendons exhibited progressive degenerative changes, abnormal collagen type III production, increased cell apoptosis, and weakened mechanical properties. When intervention was applied at day 7 for another 6 days by using cyclic tensile mechanical stimulation (6% strain, 0.25 Hz, 8 h/day) in a bioreactor, the pathological changes and mechanical properties were almost restored to levels seen in healthy tendon. Our results indicated that a proper biomechanical environment was able to rescue early‐stage pathological changes by increased collagen type I production, decreased collagen degradation and cell apoptosis. The ex vivo model developed in this study allows systematic study on the effect of mechanical stimulation on tendon biology. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:1888–1896, 2015.